2021
DOI: 10.7554/elife.60546
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of innate odor preference depends on spontaneous and experiential activities during critical period

Abstract: Animals possess an inborn ability to recognize certain odors to avoid predators, seek food and find mates. Innate odor preference has been thought to be genetically hardwired. Here we report that acquisition of innate odor recognition requires spontaneous neural activity and is influenced by sensory experience during early postnatal development. Genetic silencing of mouse olfactory sensory neurons during the critical period has little impact on odor sensitivity, discrimination, and recognition later in life. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 100 publications
(156 reference statements)
1
24
0
Order By: Relevance
“…Error bars denote SEM. Note that when presented with easier (less similar) odor pairs, MRT and SRT mice exhibit similar discrimination performance [ 74 ]. E. Occupancy, activation, and discrimination capacity effects in noses where each glomerulus received only 1% of its activation from each of the eight secondary receptors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Error bars denote SEM. Note that when presented with easier (less similar) odor pairs, MRT and SRT mice exhibit similar discrimination performance [ 74 ]. E. Occupancy, activation, and discrimination capacity effects in noses where each glomerulus received only 1% of its activation from each of the eight secondary receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of OSN convergence onto individual glomeruli has long been hypothesized to contribute to odor discrimination capabilities [ 56 , 71 73 ]. We asked whether a modest disruption of this convergence specificity on the scale demonstrated by Kir2.1 (MRT) mice would yield impairments in discrimination sensitivity when presented with tests rendered difficult owing to low concentrations or highly similar odorant mixtures; notably, Kir2.1 MRT mice exhibit no significant impairments in performance when presented with easier discrimination tasks [ 74 ]. First, we performed a cross-habituation assay between 30/70 and 70/30 ratio mixtures of four odor pairs ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from several neural systems have demonstrated that neuronal activity and Ca 2+ signaling play a vital role in the coordination and control of neuronal refinement (Golovin et al, 2019;Kanamori et al, 2013;Kano et al, 2018;Mayseless et al, 2018;Qiu et al, 2020). We therefore set out to examine the Ca 2+ dynamics during the stereotypic remodeling of γ-Kenyon cells (KCs; Figure 1 A, Lee et al, 2000), the major intrinsic cell type within the Drosophila mushroom body (MB).…”
Section: Calcium Levels In γ-Kcs Are Dynamic Upon Transition Into Metamorphosismentioning
confidence: 99%
“…TMA is a sex- and species-specific odor cue that is enriched in the urine of adult male (but not juvenile or female) Mus musculus 38,39 . While it has been reported to elicit attraction in mice 39-41 , how TMA influences social interactions is not known. Here we show that TMA, acting through TAAR5, promotes inter-male aggression, revealing a single, defined main olfactory input that drives a key social behavior in mammals.…”
Section: Introductionmentioning
confidence: 99%